Pengaruh Experiental Marketing dan Citra Perusahaan Terhadap Kepuasan Nasabah Pembiayaan Multiguna Sepeda Motor di Bank Sumut KCP Syariah Rantauprapat - Ayu Rizkia Hutagaol; Dewi Manda Anggraini (Transformasi: Journal of Economics and Business Management, 2024)
Experiential marketing's importance and This study is primarily driven by a desire to understand how Bank Sumut KCP Syariah's corporate image impacts customer satisfaction in Rantauprapat, North Sumatra. The research strategy used in this study is a quantitative correlational approach. The term "purposeful sampling" describes one method of collecting samples. Respondents to the survey serve as the primary data collectors for this investigation. Data analysis nowadays makes use of a variety of tools, including multiple linear regression analysis, classical assumption testing, and hypothesis testing. This study aims to examine the relationship between experiential marketing, corporate image, and customer happiness at North Sumatra's Bank Sumut KCP Syariah Rantauprapat. The following outcomes were derived from the SPSS 26 5% significance level test. (1) Experiential marketing has a positive and substantial impact on customer satisfaction. The findings of the determination coefficient test and the regression coefficient both corroborate this, demonstrating that experience marketing contributes 0.401, or 40.1%, to consumer satisfaction with multipurpose motorbike finance. A significance level of (0.000 < 0.05) is used. The impact of corporate image on customer satisfaction is positively and significantly correlated with 0.401 or 40.1% of customer satisfaction, as shown by the coefficient of determination test, with a significance level of (0.003 < 0.05) and a regression coefficient of 0.389. (3) The positive F_count value of 27.740 demonstrates that experiential marketing and corporate image surpass the F_table value of 3.11 at a significance threshold of 0.000 < 0.05. Coefficient of determination values of 0.401, or 40.1%, further demonstrate that experiential marketing and corporate image variables are substantial results determinants. Other factors account for 59.9% of the total, with multipurpose motorbike financing making up 40.1%.